Achieving a Large Driving Force on Triboelectric Nanogenerator by Wave‐Driven Linkage Mechanism for Harvesting Blue Energy toward Marine Environment Monitoring. Issue 5 (16th December 2022) - Han, Jiajia; Liu, Yuan; Feng, Yawei; Jiang, Tao; Wang, Zhong Lin
Abstract: Water wave energy is regarded to be a promising renewable energy source to relieve the pressure of fossil energy shortage and achieve a sustainable future. A cylindrical wave‐driven linkage mechanism triboelectric nanogenerator (WLM‐TENG) with unidirectional rotation is designed and fabricated to effectively harvest water wave energy. The enormous force generated by water waves, which is up to 424.3 N m −2, is used to drive the TENG through its simple and smart mechanical structure. This force allows the rotor to overcome the large resistance caused by the full contact between rabbit furs and electrodes. The output current can reach about 30 µA and the output power arrives at 50 mW. Moreover, self‐powered applications powered by the WLM‐TENG are successfully demonstrated, including indicating light‐emitting diodes (LEDs), multifunctional barometer, portable anemometer, and multifunctional water quality detection pen. This work renders an effective approach to harness the enormous force generated by the water waves, enhancing the water wave energy harvesting ability of the TENG, toward practical applications of marine environment monitoring. Abstract : A cylindrical wave‐driven linkage mechanism triboelectric nanogenerator (WLM‐TENG) can effectively harness the enormous force generated by water waves to produce electricity, enhancing the water wave energy harvesting ability of the TENG. Self‐powered applications powered by the WLM‐TENG are successfully demonstrated to be feasible for practical marine environment monitoring.